Developments in antimicrobial polymers. Issue 4 (29th November 2016) - Ren, Wei; Cheng, Weiren; Wang, Guan; Liu, Ye
ABSTRACT: Effective antimicrobial polymers have been attracting more interests because of the low propensity to cause drug‐resistant microorganisms. The recent progresses in antimicrobial polymers are updated according to the action approaches, that is, antimicrobial polymers with free mobility or fixed on surfaces, respectively. Free antimicrobial polymers kill pathogens majorly via electrostatic interaction followed by disruption of the cell membranes; strong antimicrobial activity of primary/secondary amines, new chemical units, and peptides without facial amphiphilicity are highlighted; and the dependences on amphiphilicity, topology, and self‐assembly profiles are summarized. Antimicrobial polymers fixed on surfaces kill pathogens via interaction with the cell membranes of pathogens via electrostatic or hydrophobic interaction; approaches to antimicrobial surfaces based on covalently grafting, anchoring, and bulk‐mixing of polymers are summarized; and new designs of sustainable antimicrobial surfaces and hydrogels are highlighted. Deep biology understanding and development strategies of materials are suggested for the future. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 632–639 Abstract : Antimicrobial polymers are promising to substitute small molecular antibiotics without causing fatal drug‐resistant superbugs because of the action via disruption of the cell membranes. Polymers containing certain types of amines and new chemical units, with simple topology and suitable morphology, are developed to kill bacteria effectively with low toxicity. Antimicrobial polymers are also fixed onto the surfaces via new covalent grafting, anchors, and bulk mixing, and it is promising to produce sustainable antimicrobial surfaces.